Optimasi Manajemen Stok Melalui Pengembangan Aplikasi Inventarisasi Real-Time di PT Carefast - Gulo, Isati; Ratnasari, Anita (Jurnal Ilmiah Sains dan Teknologi, 2026)
PT Carefast faces significant challenges in stock management due to its reliance on a manual system using written records and spreadsheets, which is prone to human error, data inconsistency, and information delays. These limitations hinder operational effectiveness and slow down decision-making. This research aims to design and develop a web-based, real-time inventory application to optimize stock management by increasing efficiency and accuracy, minimizing human error, and supporting decision-making with accurate, up-to-date data. The development methodology used is Extreme Programming (XP), utilizing PHP, the Laravel framework, and a MySQL database. The proposed application provides key functionalities such as master data management, recording of incoming and outgoing goods, a structured goods procurement approval workflow for Secretaries, Business Heads, and Directors, and instant report generation. The implementation of this system is expected to be a strategic solution for PT Carefast to replace manual processes, improve transparency, and accelerate information flow.